2016
DOI: 10.5723/kjcs.2016.37.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of School Adjustment Between Risky Neighborhood Environment and Adolescent Drinking and Smoking

Abstract: To prevent adolescent drinking and smoking, this study proposed a strategy based on the ecological perspective. Methods: The study applied multilevel moderated logistic regression analysis on nationally representative individual-level (2,046 9th grade adolescents) and neighborhood-level (92 geographic areas) data. Results: There was a positive association between risky neighborhood environments (e.g., rate of smoking, drinking, and presence of saloon/bars accommodation) and rates of adolescent drinking and smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In this study, exposure to harmful environments was a factor that affected the experience of runaway female at-risk adolescents; female at-risk adolescents who were exposed to harmful environments had a 1.97 times higher amount of sexual intercourse experiences as compared with those who had not experienced such exposures. This finding agrees with those of previous reports that reported that harmful environmental variables were positively correlated with juvenile delinquency [26] and that harmful environments could induce deviant behaviors among adolescents [12]. The use of pubs among Korean at-risk adolescents was reported to be 48.4%, which is 12.8 times higher than the 3.8% figure observed among non-at-risk adolescents; the use of entertainment and karaoke bars was 21.5%, 18 times higher than that observed among non-at-risk adolescents (1.2%); and the use of multi-rooms/room cafes was 20.5%, indicating that exposure to harmful environments had reached a serious level (one out of every five at-risk adolescents had experienced exposure to risky environments) [11].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, exposure to harmful environments was a factor that affected the experience of runaway female at-risk adolescents; female at-risk adolescents who were exposed to harmful environments had a 1.97 times higher amount of sexual intercourse experiences as compared with those who had not experienced such exposures. This finding agrees with those of previous reports that reported that harmful environmental variables were positively correlated with juvenile delinquency [26] and that harmful environments could induce deviant behaviors among adolescents [12]. The use of pubs among Korean at-risk adolescents was reported to be 48.4%, which is 12.8 times higher than the 3.8% figure observed among non-at-risk adolescents; the use of entertainment and karaoke bars was 21.5%, 18 times higher than that observed among non-at-risk adolescents (1.2%); and the use of multi-rooms/room cafes was 20.5%, indicating that exposure to harmful environments had reached a serious level (one out of every five at-risk adolescents had experienced exposure to risky environments) [11].…”
Section: Discussionsupporting
confidence: 93%
“…The 2016 national survey of adolescent risk behaviors [1] reported that 6.0% of female adolescents were found to be Internet and Smartphone addicts, which was about twice as high as the 3.2% found among male students; this finding showed the potential risks posed by exposure to risky behaviors among female adolescents. Therefore, considering that exposure to harmful environments, such as adult videos and harmful Internet sites, is a mediator for adolescents' misbehaviors, and careful attention should be payed to the sexual health of runaway female at-risk adolescents [12]. Furthermore, social and environmental factors, such as access to harmful environments, can create social problems, which, in turn, can induce runaway behaviors [2,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They go beyond the limit of space and time, creating opportunities to come into contact with others in similar age groups over a wider geographical area. As a result, they are exposed to more various harmful environments including drinking, smoking, intake of harmful drugs, and criminal acts such as pickpocketing and theft (Howard et al, 2012;S. Kim & Han, 2016;Yoo et al, 2012).…”
mentioning
confidence: 99%
“…The use rate of multirooms/room cafes is 20.5%, which indicates that one of five at-risk youth use such places. Exposure to harmful environments, including exposure to both harmful places and harmful media, has been shown to play a mediating role on problematic behavior among adolescents (S. Kim & Han, 2016), and the experience of going to harmful places often leads to running away from home, causing social problems (Cho, 2012;S. Kim & Han, 2016;Lim et al, 2014).…”
mentioning
confidence: 99%